PENGARUH TINGKAT PENDIDIKAN TERHADAP KINERJA PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SULAWESI SELATAN: Universitas Muhammadiyah Makassar - Rosinta; Andi Mappatompo; Sri Andayaningsih (PT. Media Edutama Nusantara, 2024)
This study aims to determine and analyze the influence of education level on employee performance at the Industry and Trade Service of South Sulawesi Province. The research method used in the study is a quantitative method with an associative approach. The method for collecting data is through observation, questionnaires and documentation with a population of 115 employees and an interesting sample using the slovin formula so that the number of samples obtained is 89 employees with the data analysis method used is simple linear regression analysis processed through the assistance of Statistical Package for the Social Science (SPSS) Software Version 27. Based on the results of this study, it shows that the results of the t-test obtained on the education level variable (X) on employee performance (Y) obtained tcount 8.674> ttable 1.987 with a significance level of 0.05. The results of this study indicate that there is a positive and significant influence of the education level variable on employee performance at the Industry and Trade Service of South Sulawesi Province